New Paradigm of Outcome-Based Education – A Higher Education Boon - G. Ganesh Narayanan, Dr.K. Bala Sathya, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Outcome-Based Education (OBE) is a vibrant model and considered as a giant leap forward to improve higher education and assists all graduates contend with their global counterparts. It is a student-centered tutoring conception that focuses on measuring student performance through outcomes. The Higher Education Institutions should frame appropriate course outcome, program outcome and these outcome should correlate with institutional objectives. But the actual success lies in the effective implementation and rigid accreditation process to ensure the quality of education. Hence, it is imperative to analyze the strength, weakness of the model and practical difficulties in case of implementation. This study reveals basic concepts, Implementation Strategies and OBE Practices and standards. The OBE-Steering Committee in each HEI offers ideas to frame Newfangled Curriculum with finest outcome and effective teaching methods with ICT tools and evaluation pattern based on blooms taxonomy.